Polyphenol Extracts From Germinated Mung Beans Can Improve Type 2 Diabetes in Mice by Regulating Intestinal Microflora and Inhibiting Inflammation - Shen, Xinting; Jiang, Xiujie; Qian, Lili; Zhang, Aiwu; Zuo, Feng; Zhang, Dongjie (Frontiers in Nutrition, 2022)
Studies have shown that inhibiting inflammation and regulating intestinal microflora imbalance is a significant factor in controlling the development of type 2 diabetes mellitus (T2DM). This experiment studied the protective effect of polyphenol extract from germinated mung beans on diabetic C57BL/6 mice. Results Fasting blood glucose (FBG) was decreased, glucose tolerance was increased, insulin resistance was decreased, serum lipid indexes in T2DM mice were improved, and the enzyme activities of alanine aminotransferase (ALT) and aspartate transaminase (AST) in serum were reduced. Meanwhile, the levels of interleukin 6 (IL-6), tumor necrosis factor-α (TNF-α), and C-reactive protein (CRP) in serum were decreased, the concentration of interleukin 10 (IL-10) in serum was increased, inhibiting the inflammatory reaction induced by diabetes and repairing the morphology of mice liver tissue. At the same time, germinated mung bean polyphenol (GMP) can regulate the main intestinal flora, Firmicutes, Bacteroidetes, and Proteobacteria in diabetic mice and can also regulate species diversity and improve intestinal flora imbalance. Taken together, the experimental conclusion is a certain dose of polyphenol extract from germinated mung beans that can improve mouse T2DM by inhibiting inflammatory reaction and regulating intestinal microflora.